NEW CONCEPT IN DENTOFACIAL ESTHETICS: THE BIOLOGICAL ASPECTS OF ADULT ORTHOPEDIC FACE MASK THERAPY: KONSEP BARU DALAM ESTETIKA DENTOFACIALDENTOFACIAL: ASPEK BIOLOGIS TERAPI TOPENG BEDAH TULANG DEWASA - Retno Pudji Rahayu; Haryono Utomo (TALENTA, 2010)
Orthopedic face mask has been introduced for more than 100 years ago, however, it is primarily indicated for growingpatients. Its effectiveness in adult patients is still questionable. It is thought that in non growing adults the degree oforthopedic movement is minimal, whether dental movement i s more prominent. In addition, there is still controversial,whether patients’ compliance or the existent skeletal growth determines the treatment success. The objective of this studywas to propose a new concept for adult orthopedics face mask therapy ba sed on functional and biological mechanismsinvolved in dentofacial remodeling . Conventional face mask therapy only depended on duration, magnitude andunidirectional elastic forces. In the reviewed case report, the inspiration for a new concept was evolv ed from themultidirectional forces which were resulted from continuous functional movements (i.e. chewing and speaking) duringwearing face mask. These movements may lead to stimulate additional orthopedic or skeletal movements in adult patient.The expla nation of this phenomenon could be explained not only by clinical result, but also with the biologicalmechanism of bone remodeling. In conclusion, regarding to the successful treatment result and its logical biologicalexplanation, this new concept to inc rease the effectiveness of adult orthopedic face mask therapy is likely.